2015 SBMO/IEEE MTT-S International Microwave and Optoelectronics Conference (IMOC) 2015
DOI: 10.1109/imoc.2015.7369088
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Schottky barrier diode millimeter-wave multipliers at cryogenic temperatures

Abstract: Abstract-We report on the evaluation of Schottky barrier diode GaAs multipliers at cryogenic temperatures. A GaAs Schottky barrier diode model is developed for theoretical estimation of doubler performance. The model is used to predict efficiency of doublers from room to cryogenic temperatures. The theoretical estimation is verified experimentally using a 78 GHz doubler cooled down to 14 K. The observed efficiency improvement due to cooling is approximately 4 % per 100 degrees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…In this paper, the performance of GaAs Schottky-based multipliers at cryogenic temperatures are studied. The paper expands on the author's previous study [6] on the efficiency at cryogenic temperatures for a 78 GHz frequency doubler reported in the literature [7]. The paper is structured as follows.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…In this paper, the performance of GaAs Schottky-based multipliers at cryogenic temperatures are studied. The paper expands on the author's previous study [6] on the efficiency at cryogenic temperatures for a 78 GHz frequency doubler reported in the literature [7]. The paper is structured as follows.…”
Section: Introductionmentioning
confidence: 87%
“…A first-order thermal network, similar to the one described in [6], is included into our model formulation to simulate self-heating effects.…”
Section: Self-heatingmentioning
confidence: 99%
“…The graph in Figure shows estimated using the model described in Ref. and measured efficiency versus temperature.…”
Section: Comparison Of Estimated and Measured Datamentioning
confidence: 99%
“…One of the examples is dynamic nuclear polarization (DNP) systems, where polarization efficiency relies on availability of millimeter-wave radiation [1]. This work presents a family of doublers covering frequency bands which are of interest for 3.35 T and 6.7 T DNP systems [2] and is a first step towards partially integrating millimeter-wave sources into DNP cavities. The circuits are designed for low insertion loss and fabricated in a high-speed InP DHBT circuit technology [3] developed at III-V Lab.…”
Section: Introductionmentioning
confidence: 99%